Satureja khuzistanica Jamzad essential oil prevents doxorubicin-induced apoptosis via extrinsic and intrinsic mitochondrial pathways - Ali Al Seyedan; Omid Dezfoulian; Masoud Alirezaei (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: In addition to hepato-cardiotoxicity, doxorubicin (DOX) also induces nephrotoxicity which is considered as the limiting factor for this drug in cancer therapy. The effect of carvacrol, the main active ingredient of Satureja khuzistanica Jamzad essential oil (SKEO), in the amelioration of DOX- induced cardiotoxicity is well established. The aim of the present study was to evaluate the possible protective effects of SKEO against DOX-induced nephrotoxicity. Experimental approach: SKEO was intraperitoneally administered at 50, 100, and 200 mg/kg to male Wistar rats for 12 consecutive days. Five groups of animals including negative control (saline), vehicle (Tween® 20), SKEO50, DOX (at 8th day of treatment), and SKEO50 + DOX were assessed. Findings/Results: Creatinine, urea concentrations, and caspase-3 activity significantly elevated in the serum of DOX treated group in contrast to other groups after injection of a single dose of DOX (20 mg/kg i.p.), however, SKEO reduced glutathione peroxidase and caspase-3 activity against other groups while SKEO + DOX was also significantly reduced caspase-3 activity against DOX group. Other biochemical markers changes were not significant. Immunohistochemical assessment unveiled that SKEO + DOX improved the activity of Bcl-2 family proteins (Bax and Bcl-2) and caspase-8 protein to the advantage of cell survival in both intrinsic mitochondrial and extrinsic pathway down streamed to the terminal caspase-3 apoptotic molecule., Conclusion and implications: It was concluded that SKEO could have influential effects against apoptosis induced by DOX, but not improperly ameliorate oxidative stress.